The white tiger - Adiga, Aravind (New York Free Press, 2008)
A stunning literary debut critics have likened to Richard Wright?s Native Son, The White Tiger follows a darkly comic Bangalore driver through the poverty and corruption of modern India?s caste society. ?This is the authentic voice of the Third World, like you've never heard it before? (John Burdett, Bangkok 8).
Keywords: Chauffeurs--India--Bangalore--Fiction.